PENERAPAN REHABILITASI DAN PENGOBATAN PASIEN NARKOTIKA DALAM PASAL 53 DAN PASAL 54 UNDANG- UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Krismanko Padang; Yusuf Setyadi (JOURNAL OF LAW AND NATION, 2022)
Article 54 of Law Number 35 of 2009 stipulates that Narcotics addicts and victims of Narcotics abuse are required to undergo medical rehabilitation and social rehabilitation. This regulation is categorized as a “special” regulation that deviates from the general criminal system prevailing in Indonesia. It is called "special" because it applies a double track criminal system, namely a criminal system that produces two types of sanctions: criminal and action. In this case, all court institutions in Indonesia are required to provide action sanctions, namely the rehabilitation of all Narcotics abusers and dealers sentenced to imprisonment or the death penalty. Rehabilitation is regulated in CHAPTER IX of Law Number 35 of 2009. Rehabilitation is divided into two, namely Medical Rehabilitation and Social Rehabilitation. Article 53 concerning Treatment is stated in paragraphs (1) to (3) regarding the ability of patients who are being rehabilitated to store, carry, and use Narcotics Category II or Category III at the request of a doctor and medical indications. Moving on from the regulation, the author will elaborate with the juridical- normative study method and descriptive-analysis from primary and secondary legal sources. The problem of the study that will be resolved is to what extent these regulations can be applied by doctors and what conditions must be met? Does the regulation not conflict with other laws and regulations? How effective is the method based on medical research? Through these questions, the author analyzes the main issues that arise in the material of Article 54 Number 35 of 2009 concerning Narcotics.